Short-Term Hip Fracture Outcomes during the COVID-19 Pandemic - Walters, Samuel; Raja, Hassan; Ahmad, Rachel; Tsitskaris, Konstantinos (The Surgery Journal, 2022)
Introduction Despite many significant changes as a result of the coronavirus disease 2019 (COVID-19) pandemic, and reductions in overall trauma workload, patients with fragility hip fractures continued to present to hospital. As we plan for ongoing service provision during future waves of the pandemic, valuable lessons can be learned from patients that have been treated surgically during the “first wave.”Methods All patients admitted to our center (a busy District General Hospital in London, United Kingdom) with a hip fracture during a 13-week period representing the initial rise (“United Kingdom first wave”) in COVID-19 cases, from February 17th to May 17th, 2020 (study group) were compared with hip fracture patients from the equivalent 13-week period in February to May 2019 (control group). The primary outcome was 30-day mortality, and additional information was collected in terms of length of stay (LOS), SARS-CoV-2 antigen testing, and cause of death.Results During the COVID-19 study period, 69 patients were admitted with a hip fracture, compared with 70 patients in the control group (p = 0.949). There was no significant difference in 30-day mortality between the two groups (5.8 vs. 7.1%, p = 0.747). Mean LOS was shorter in the COVID-19 period compared with the control group (11.6 vs. 19.6 days, p <0.001, effect size 0.572).Forty-six patients (66.7%) had a SARS-CoV-2 antigen swab test, as testing was not available in the early period, and 10 patients (14.5%) tested positive. None of the patients, who presented before the antigen testing was available, had clinical suspicion of COVID-19 retrospectively. Two “COVID-19 positive” patients (20%) died within 30 days of admission.Conclusion We report reassuring short-term results demonstrating no statistically significant difference in the 30-day mortality rate of hip fracture patients admitted during the United Kingdom's first wave of the COVID-19 pandemic compared to the equivalent period in the previous year. Hip fracture incidence remained stable, and LOS was reduced, likely due to recent departmental changes as well as a drive to discharge patients quickly during the pandemic. We agree with existing reports that elderly hip fracture patients with COVID-19 have a higher risk of perioperative mortality, however, our results suggest that overall mortality for the whole hip fracture population was similar to the previous year, in which deaths were more commonly attributed to respiratory infections associated with other pathogens. Further work may be needed to evaluate the outcomes during subsequent waves of the pandemic as mutations in the virus and conditions may affect outcomes.
Keywords: hip fracture; length of stay; mortality; 30-day mortality; COVID-19; SARS-CoV-2